The Improvement of English Speaking Competence of Philology Students Through Sociodrama Technology - Kohhorova Madinahon Abdukodir Kizi (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2026)
This study investigates the effectiveness of an improved pedagogical system based on sociodrama technology for developing English speaking competence among first-year undergraduate students majoring in Philology and Language Teaching (English). The research was designed to address the growing need for more interactive, student-centered, and practice-oriented approaches in foreign language instruction at higher education institutions. The experimental work was conducted in four stages: diagnostic and prognostic, organizational-preparatory, practical, and generalizing. During the initial stage, curricula, syllabi, and educational materials were carefully analyzed, while classroom observations and questionnaire surveys were used to identify the main difficulties encountered in teaching and learning English speaking skills. At the practical stage, sociodrama-based activities, methodological recommendations, and specially designed teaching materials were systematically introduced into classroom instruction as well as independent learning tasks. The participants were divided into a control group of 30 students and an experimental group of 32 students. The final results revealed a clear advantage for the experimental group: 44% of students achieved grade 5, 41% received grade 4, and only 15% received grade 3, whereas in the control group the corresponding figures were 17%, 37%, and 46%. These findings demonstrate that sociodrama technology has a positive impact on learners’ motivation, communicative activity, creativity, confidence, and contextual speaking performance. The study confirms that the improved pedagogical system can be effectively implemented in higher education foreign language instruction to enhance students’ oral communication skills and overall language competence